Potensi Objek Wisata Pulau Lusi Porong Terhadap Perekonomian Masyarakat Sekitar - Adinda Bahar Abrianti; Wahyu Eko Pujianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Lusi Island is a river island that was formed from a natural disaster, where this river island was formed from silt deposited as a result of being dumped into the Porong river. Lusi Island has an area of 83.4 hectares where this island is located at the mouth of the Porong River, Jabon District, Sidoarjo Regency. Many of these mud deposits were then planted with mangrove plants. The Lapindo Mud was the first cause that caused rapid deposition and also affected the development of the area of Lusi Island. In 2017 Lusi Island was managed by the Ministry of Maritime Affairs and Fisheries where previously Lusi Island was managed by the Sidoarjo Lapindo Mud Management Executing Agency (BPLS). The Ministry of Marine Affairs and Fisheries has plans to utilize Lusi Island as a place for restoration and learning about mangrove plants, where the Ministry of Maritime Affairs and Fisheries is also building various facilities to support and support Lusi Island as a place of learning and also a tourist spot after the Sidoarjo Lapindo mudflow disaster. In this study, the researcher wanted to conduct a direct review of the field and also wanted to find out how big the impact of this Lusi Island tourist attraction was on the economy of the surrounding community. Researchers conducted research with a quantitative descriptive system where researchers in collecting data used analysis SWOT.